Preoperative risk assessment and optimization integrating surgical and anesthetic principles and practices: a national survey for internists - Marc-Antoine Lepage; Annie Lecavalier; Gabriele Baldini; Ning-Zi Sun; Amal Bessissow (Perioperative Medicine)
Abstract Background The integration of procedure-specific risks into preoperative patient assessment and optimization are crucial aspects of perioperative care. However, data on internists’ knowledge of surgical and anesthetic principles and practices are limited. We thus sought to identify internists’ knowledge gaps in terms of surgical- and anesthetic-specific risk factors and characteristics. Methods An open and voluntary e-survey was conducted via LimeSurvey between April and July 2021 to evaluate Canadian internists’ knowledge of surgical and anesthetic principles and practices. The survey included the perceived importance and knowledge of several key surgical and anesthetic aspects, such as surgery duration, procedure-specific cardiac risk, bleeding risk, and thrombotic risk. It also assessed pre- and post-survey self-reported confidence levels in one’s knowledge of these characteristics. Finally, we investigated how internists optimize some of the preoperative risks. Results A total of 173 Canadian internists opened the survey link, and 121 completed it (completion rate 70%). While the majority of respondents considered surgical and anesthetic principles and practices as important, most identified knowledge gaps. Participants generally estimated surgery duration and procedure-specific cardiac risk adequately. However, they tended to underestimate procedure-specific bleeding risk for general (58%) and orthopedic (76%) surgeries and to overestimate procedure-specific thrombotic risk for vascular (63%) and genitourinary (60%) surgeries. Furthermore, there is a lack of consensus regarding the appropriate hemoglobin A1c target and 0% of respondents reported using the guideline-suggested hemoglobin threshold for investigation and intervention. Conclusions Overall, our findings identify significant knowledge gaps among Canadian internists in preoperative assessment of procedure-specific risk factors and can be used to inform both the development of educational initiatives and future research to improve the quality of preoperative patient care.